Scientific Opinion on the safety and efficacy of Ronozyme HiPhos GT (6‐phytase) as feed additive for poultry and pigs - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2012)
Abstract The additive Ronozyme® HiPhos is an enzyme preparation containing 6‐phytase produced by a genetically modified strain of Aspergillus oryzae. EFSA issued an opinion on the safety and efficacy of this additive under two different formulations, one solid (M) and one liquid (L), when used as a feed additive for poultry and swine. The applicant is now seeking the authorisation of a new solid formulation (GT). The safety for the consumer, the user and the environment, as well as the safety aspects of the genetic modification, have already been assessed. The FEEDAP Panel considered that the new formulation is not expected to introduce hazards to the target species, consumers, users or the environment not already considered in the previous application. The new formulation is expected to be as efficacious as the other two, and this has been confirmed in two efficacy studies with the GT form.